Attu boy: a young Alaskan's WWII memoir - Golodoff, Nick, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2015)
In the quiet of morning, exactly six months after Pearl Harbor, the Japanese touched down on American soil. Landing on the remote Alaska island of Attu, they assailed an entire village, holding the Alaskan villagers for two months and eventually corralling all survivors into a freighter bound for Japan. One of those survivors, Nick Golodoff, became a prisoner of war at just six years old. He was among the dozens of Unangan Attu residents swept away to Hokkaido, and one of only twenty-five to survive. Attu Boy tells Golodoff's story of these harrowing years as he found both friendship and cruelty at the hands of the Japanese. It offers a rare look at the lives of civilian prisoners and their captors in WWII-era Japan. It also tells of Golodoff's bittersweet return to a homeland torn apart by occupation and forced internments. Interwoven with other voices from Attu, this richly illustrated memoir is a testament to the struggles, triumphs, and heartbreak of lives disrupted by war.
List of Figures -- Preface by Brenda Maly -- Introduction -- A Young Boy's Experience during World War II -- Attu before the War -- Prewar Fears and Clues about Japanese Invasion -- The Japanese Invasion, June 7, 1942 -- Life as a Japanese POW -- Return and Resettlement -- Nick's Connection to Japan -- Reflections on Life in Atka -- Growing Up and Going to School -- Left Behind by the Military -- Working Life -- Hunting, Fishing, and Wildlife -- Atka Is Far Away from Anywhere Else -- Learning from the Elders -- Relatives from Attu -- Commentary and First-Person Accounts -- Attu before the War -- Prewar Fears and Clues about Japanese Invasion -- The Japanese Invasion, June 7, 1942 -- Life as a Japanese POW -- Return and Resettlement -- Nick's Connection to Japan -- Epilogue -- Appendix: Attu Prehistory and History -- Bibliography.
Keywords: Attu Island (Alaska) -- Biography; Attu, Battle of, Alaska, 1943 -- Personal narratives, American; Prisoners of war -- United States; Prisoners of war -- Japan -- Shiritsu Otaru Bungakkan; World War, 1939-1945 -- Alaska -- Aleutian Islands; Aleuts -- Biography; Attu Island (Alaska) -- History; Attu Island (Alaska) -- Social life and customs; Golodoff, Nick